MEDIA PEMBELAJARAN PENGENALAN NAMA-NAMA HEWAN DAN TUMBUHAN BAGI ANAK USIA DINI: Learning Media, Teachers, Students - Mulyati, Sri (LP2M Universitas Nurdin Hamzah, 2018)
This study aims to improve the ability or understanding of early childhood of Al-Fajar Kindergarten in getting to know animals and plants.This research was conducted in collaboration with teachers. The study participants were teachers and students of TK Al-Fajar Jambi, amounting to 12 students. In designing the application made there is a quiz and guess images that aim to know the extent to which students' mastery of the material and motivate students in learning. The research was conducted in three stages: field research, library research and laboratory research.The results of the research are as follows: (a) The teacher guides the students how to use the application. (b) Students practice according to what the teacher explains (c) Students listen to the material submitted by the application. (d) Students are confronted with quizzes and guess images. (e) the teacher takes the score from the quiz or guess the picture. (f) The average score obtained by students is 80 points. It can be concluded that students' learning motivation improved after using learning method using audio visual. Suggestion of research that is expected application use 3D image